Y=10(3)^3-12(3)
y=270-36
y=234
8/x-7=7/2
16=7(x-7) cross multiply
16=7x-49
-7x=-49-16
-7x=-65 divides each side by -7
-7x/7=-65/7
X=65/7
Alternative form
X=92/7
Which is 1st options in your questions.
Hope this helps!
Answer:
The method used is substitution method
x = 2, y = -6
Step-by-step explanation:
Given the simultaneous equation
Y = −3x ..... 1
4x + y = 2 ... 2
Substitute equation 1 into 2
4x + (-3x) = 2
4x - 3x = 2
x = 2
Get y:
y = -3x
y = -3(2)
y = -6
<em>Hence the value of (x, y) is (2, -6)</em>
<em></em>
<em></em>